The Effect of Managerial Competency and Teacher Performance on the Learning Achievement of Private Vocational Schools, Se-Babat Supat District - Pempen, Ni Wayan; Fitria, Happy; Eddy, Syaiful (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine the effect of principal managerial competence and teacher performance on student achievement. The location of this research was carried out in SD Negeri all Babat Supat District. This type of research is a quantitative study with a determination design using an ex post facto research design. The sample in this study was the total of all teachers in SD Negeri in Babat Supat District, consisting of 174 teachers. data collection techniques using a questionnaire. The data analysis technique used quantitative descriptive analysis techniques and multiple regression. The results of this study indicate that 1) there is a significant influence between the managerial competence of the principal on the learning achievement of the students of SD Negeri in Babat Supat District; 2) there is a significant influence between teacher performance on student achievement in SD Negeri in Babat Supat District; 3) there is a significant influence jointly between principal managerial competence and teacher performance on student achievement of SD Negeri in Babat Supat District.